2016
DOI: 10.1038/hgv.2016.38
|View full text |Cite
|
Sign up to set email alerts
|

Deep resequencing of CFTR in 762 F508del homozygotes reveals clusters of non-coding variants associated with cystic fibrosis disease traits

Abstract: Extensive phenotypic variability is commonly observed in individuals with Mendelian disorders, even among those with identical genotypes in the disease-causing gene. To determine whether variants within and surrounding CFTR contribute to phenotypic variability in cystic fibrosis (CF), we performed deep sequencing of CFTR in 762 patients homozygous for the common CF-causing variant, F508del. In phase 1, ~200 kb encompassing CFTR and extending 10 kb 5′ and 5 kb 3′ of the gene was sequenced in 486 F508del homozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 48 publications
(54 reference statements)
5
32
0
Order By: Relevance
“…We referenced p.Phe508del complex alleles in which the variation in cis is within the coding region and indicated their frequency by combined results found in the literature (Diana et al., ; Fichou et al., ; Vecchio‐Pagan et al., ), the CFTR‐France Database (Bareil et al., ; Claustres et al., ). We also analyzed 100 exon 12 and 153 exon 19 of p.Phe508del containing chromosomes in the French population (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We referenced p.Phe508del complex alleles in which the variation in cis is within the coding region and indicated their frequency by combined results found in the literature (Diana et al., ; Fichou et al., ; Vecchio‐Pagan et al., ), the CFTR‐France Database (Bareil et al., ; Claustres et al., ). We also analyzed 100 exon 12 and 153 exon 19 of p.Phe508del containing chromosomes in the French population (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We referenced p.Phe508del complex alleles in which the variation in cis is within the coding region and indicated their frequency by combined results found in the literature (Diana et al, 2016;Fichou et al, 2008;Vecchio-Pagan et al, 2016), the CFTR-France Database ( of which were identified in discrete cases. For the five complex alleles found more than once, frequencies ranged from 0.3% up to 6.4%.…”
Section: Pphe508del Complex Allele Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…Several complex alleles (e.g., p.[Arg74Trp;Val201Met;Asp1270Asn], p.[Phe508del;Ile1027Thr], or p.[Ser1251Asn;Phe508Cys] are frequent and well known. However, rare associations are also reported in CFTR ‐France, for example, a dozen variants are described in cis of p.Phe508del, some of them not found in the recent article about resequencing of p.Phe508del homozygotes (Vecchio‐Pagán et al., ).…”
Section: Current Content Of Cftr‐francementioning
confidence: 99%
“…Some benign variants were misclassified as CF‐causing because they were observed in patients with CF but in the context of complex alleles with CF‐causing variants, such as c.3080C>T (p.Ile1027T) reported in cis with c.1521_153del (p.Phe508del; Baatallah et al, ). Notably, a total of 28 such variants have been described in complex alleles in CFTR ‐France, and more than 20 variants have been linked to c.1521_1523del (p.Phe508del; Vecchio‐Pagán et al, ). As other illustrations of complex alleles, among the 27 “frequent” variants (Group 1), c.220C>T (p.Arg74Trp), c.601G>A (p.Val201Met) and c.3808G>A (p.Asp1270Asn) have been described in cis in CFTR ‐France in numerous patients with CFTR‐RD, as well as c.1727G>C (p.Gly576Ala) and c.2002C>T (p.Arg668Cys; El‐Seedy et al, ).…”
Section: Introductionmentioning
confidence: 99%